Step-by-step explanation:
here's the solution :-
1.) =》f = 90°
( because angle made by diameter on circumference of the circle measures 90° )
2.) =》here,
g + f + 56° = 180°
( because the sum of all interior angles of the triangle measures 180° )
=》g + 90° + 56° = 180°
=》g + 146° = 180°
=》g = 180° - 146°
=》g = 34°
3.) h = 56°
( since, they form alternate interior pair which are equal )
Answer:
Thats false
Step-by-step explanation:
When you multiply by a power your basically multiplying that number b itself 10x except for 1
Answer:
5/7
Step-by-step explanation:
Answer:
Dont ask me
Step-by-step explanation:
Okay!!!!!
∫(t = 2 to 3) t^3 dt
= (1/4)t^4 {for t = 2 to 3}
= 65/4.
----
∫(t = 2 to 3) t √(t - 2) dt
= ∫(u = 0 to 1) (u + 2) √u du, letting u = t - 2
= ∫(u = 0 to 1) (u^(3/2) + 2u^(1/2)) du
= [(2/5) u^(5/2) + (4/3) u^(3/2)] {for u = 0 to 1}
= 26/15.
----
For the k-entry, use integration by parts with
u = t, dv = sin(πt) dt
du = 1 dt, v = (-1/π) cos(πt).
So, ∫(t = 2 to 3) t sin(πt) dt
= (-1/π) t cos(πt) {for t = 2 to 3} - ∫(t = 2 to 3) (-1/π) cos(πt) dt
= (-1/π) (3 * -1 - 2 * 1) + [(1/π^2) sin(πt) {for t = 2 to 3}]
= 5/π + 0
= 5/π.
Therefore,
∫(t = 2 to 3) <t^3, t√(t - 2), t sin(πt)> dt = <65/4, 26/15, 5/π>.